PENGARUH PROMOSI DAN LAYANAN TERHADAP KEPUTUSAN NASABAH KREDIT USAHA MIKRO DI PT. BANK MANDIRI (PERSERO) TBK. CABANG TUGUMULYO MUSI RAWAS - Supriyanto Supriyanto; Murlina Nisusmiati; Fahmi Irham (Jurnal Media Ekonomi (JURMEK), 2018)
The objectives of this study are as follows: a. To determine the effect of promotion and service on the micro business credit customers at PT BANK MANDIRI (PERSERO) TBK. Tugumulyo Musi Rawas Branch, b. To determine the customers' business credit at PT BANK MANDIRI (PERSERO) TBK. Tugumulyo Musi Rawas Branch, c. To determine the effect of service on the decision of micro business credit customers at PT BANK MANDIRI (PERSERO) TBK. Tugumulyo Musi Rawas Branch. Based on the results of the test, the variable that promotion variable (X1) on the micro business credit decision customers at PT. Bank Mandiri (Persero) Tbk. Tugumulyo Musi Raw branch shows that the value of t = 2.788 is greater than ttable 2,000 with a significant level = 0,000 <(α) 0.05, df (n-2) 57 - 2 = 55 is equal to 2,000, this shows Ho is rejected and is accepted and partially the promotion variable has a significant influence on the decision of micro business customers at PT. Bank Mandiri (Persero) Tbk Tugumulyo Musi Rawas Branch. Based on the results of the t test, the service variable (X2) on the micro business credit decision customers at PT. Bank Mandiri (Persero) Tbk. The Tugumulyo Musi Raw branch shows that the value of t count = 3.852 is greater than ttable 2,000 with a significant level = 0,000 <(α) 0.05, df (n-2) 57 - 2 = 55 is equal to 2,000, this shows Ho is rejected and Ha is accepted and partially service variables have a significant influence on the decision of micro business customers at PT. Bank Mandiri (Persero) Tbk Tugumulyo Musi Rawas Branch. Based on the results of the F test show show that the calculated value is 10.750> Ftable = 5.06 and the significance of the simultaneous level the significance is 0.000 <(α) = 0.05 df = n - k = 57-2-2 - 1 = 54 has a significant influence on the dependent variable, namely the decision of the customer, so that the truth is proven and the hypothesis is acceptable